Bending–Rotation Coupling in the Viscoelasticity of Semiflexible PolymersRigorous Perturbation Analysis from the Rod Limit - Xiong, Zhongqiang; Seto, Ryohei; Doi, Masao (Macromolecules, 2024)
Brownian motion and viscoelasticity of semiflexible polymers is a subject that has been studied for many years. Still, rigorous analysis has been hindered due to the difficulty in handling the constraint that polymer chains cannot be stretched along the contour. Here, we show a straightforward method to solve the problem. We consider a stiff polymer that has a persistent length L p much larger than the contour length L. We express the polymer configuration using three types of variables: the position vector of the center of mass R c, the unit vector n along the main axis, and the normal coordinates u p for bending. Solving the Smoluchowski equation for the distribution function of these variables, we calculate the equilibrium time correlation function ⟨ P (t)· P (0)⟩ of the end-to-end vector P and the complex modulus G*(ω) of dilute solution. They include the bending effect to the first order in θ ≡ L/L p and reduce to the exact results for the rigid rod in the limit of θ → 0. The rotational diffusion coefficient increases slightly by the semiflexibility because the equilibrium length of the semiflexible polymer is smaller than that of the rigid rod with the same contour length. The storage modulus shows the same asymptotic dependence G′(ω) ∼ ω3/4 predicted by Shankar, Pasquali, and Morse [J. Rheol. 2002, 46, 1111–1154]. The high-frequency viscosity is predicted to be dependent on the thickness of the semiflexible polymers.